Mitochondrial Nicotinic Acetylcholine Receptors Support Liver Cells Viability After Partial Hepatectomy - Uspenska, Kateryna; Lykhmus, Olena; Obolenskaya, Maria; Pons, Stephanie; Maskos, Uwe; Komisarenko, Serhiy; Skok, Maryna (Frontiers in Pharmacology, 2018)
Nicotinic acetylcholine receptors (nAChRs) expressed on the cell plasma membrane are ligand-gated ion channels mediating fast synaptic transmission, regulating neurotransmitter and cytokine release and supporting the viability of many cell types. The nAChRs expressed in mitochondria regulate the release of pro-apoptotic factors, like cytochrome c, in ion channel-independent manner. Here we show that α3β2, α7β2 and α9α10 nAChR subtypes are up-regulated in rat liver mitochondria 3-6 h after partial hepatectomy resulting in increased sustainability of mitochondria to apoptogenic effects of Ca2+ and H2O2. In contrast, laparotomy resulted in down-regulation of all nAChR subunits, except α9, and decreased mitochondria sustainability to apoptogenic effects of Ca2+ and H2O2. Experiments performed in liver mitochondria from α3+/-, α7-/-, β4-/-, α7β2-/-, or wild-type C57Bl/6J mice demonstrated that the decrease of α3 or absence of α7 or α7/2 subunits in mitochondria is compensated with β4 and α9 subunits, which could be found in α3β4, α4β4, α9β4 and α9α10 combinations. Mitochondria from knockout mice maintained their sustainability to Ca2+ but were differently regulated by nAChR subtype-specific ligands: PNU-282987, methyllycaconitine, dihydro-β-erythroidine, α-conotoxin MII and α-conotoxin PeIA. It is concluded that mitochondrial nAChRs play an important role in supporting the viability of hepatic cells and, therefore, may be a pharmacological target for pro-survival therapy. The concerted action of multiple nAChR subtypes controlling either CaKMII- or Src-dependent signaling pathways in mitochondria ensures a reliable protection against apoptogenic factors of different nature.